2017
DOI: 10.1016/j.atherosclerosis.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and subclinical coronary atherosclerosis: The Multicenter AIDS Cohort Study (MACS)

Abstract: Background and aims Frailty and cardiovascular disease share many risk factors. We evaluated whether frailty is independently associated with subclinical coronary atherosclerosis and whether any relationships differ by HIV-serostatus. Methods We studied 976 [62% HIV-infected] male participants of the Multicenter AIDS Cohort Study who underwent assessment of frailty and non-contrast cardiac CT scanning; of these, 747 men also underwent coronary CT angiography (CCTA). Frailty was defined as having ≥3 of 5 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Muscle mass is weakly correlated with muscle strength in MACS, 15 and muscle weakness is an component of frailty, 35 which in turn is an important prognostic marker of CVD and mortality among older adults and adults with HIV-infection. 36-38 Defining frailty by the Fried phenotype, 35 MACS found that HIV-infected men aged 50-69 were significantly more likely to be frail compared to similarly-aged HIV-uninfected men, 21, 22 and frail HIV-infected men had higher levels of inflammatory markers and immune activation compared to nonfrail HIV-infected men. 39 Frailty by the Fried definition was associated with subclinical coronary atherosclerosis in MACS, but only among HIV-uninfected men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle mass is weakly correlated with muscle strength in MACS, 15 and muscle weakness is an component of frailty, 35 which in turn is an important prognostic marker of CVD and mortality among older adults and adults with HIV-infection. 36-38 Defining frailty by the Fried phenotype, 35 MACS found that HIV-infected men aged 50-69 were significantly more likely to be frail compared to similarly-aged HIV-uninfected men, 21, 22 and frail HIV-infected men had higher levels of inflammatory markers and immune activation compared to nonfrail HIV-infected men. 39 Frailty by the Fried definition was associated with subclinical coronary atherosclerosis in MACS, but only among HIV-uninfected men.…”
Section: Discussionmentioning
confidence: 99%
“…39 Frailty by the Fried definition was associated with subclinical coronary atherosclerosis in MACS, but only among HIV-uninfected men. 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed measurement protocols and definitions for all of these covariates have been previously published. [3,8,31] Statistical analysis: All results were presented for the overall cohort, and then stratified by HIV sero-status.…”
Section: Covariatesmentioning
confidence: 99%
“…Although research shows that there are associations between frailty and CVD, few studies examine the associations between CHD diagnoses and frailty, particularly in older adults [17]. Little is known about the relationship between frailty and in-hospital mortality and readmission rates in hospitalized older patients with CHD.…”
mentioning
confidence: 99%